A university electronic educational environment as an innovative resource for professional training of future psychologists and social teachers - Irina Vladimirovna Detkova; Fatima Ramazanovna Khatit; Alexandra Vladimirovna Leontyeva; Natalya Vladimirovna Kovaleva (Вестник Майкопского государственного технологического университета)
Today an electronic educational environment is an integral innovative component of vocational education functioning. The construction of electronic educational environments in Russia is supported by government initiatives in the context of the modernization of the entire educational institution, taking into account global trends. Today, our country has accumulated a certain experience in the development and use of electronic educational resources in the educational process, which needs analysis and systematization. The research problem: what are the mechanisms of using electronic educational environment of a university in the professional training of future psychologists and social teachers? The purpose of the research is to substantiate the expediency of using electronic educational environment in the professional training of future psychologists and social teachers. The research methods used are synthesis, systematization, desk research, generalization. The research results are the following: the relevance of using the electronic educational environment of a university as an innovative resource in the professional training of future psychologists and social teachers has been confirmed; the components of the electronic educational environment of a university have been characterized; electronic resources used in educational activities for the purpose of resource and information support of psychological and pedagogical disciplines have been disclosed Key conclusions: digital service is viewed as an additional, promising innovative educational resource in the professional training of future psychologists and social educators; the components of the electronic information and educational environment of a university are the official website, an electronic library, electronic an educational environment; the effectiveness of professional training of future psychologists and social teachers is possible with the additional use of Moodle, Zoom, YouTube, Google electronic resources.